The Real Landscape Of Pulmonary Artery Hypertension Associated With Congenital Heart Disease In Vietnam National Heart Institute – Bach Mai Hospital – Vietnam - Thi Duyen Nguyen; Truong Thannh Huong (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
The Real Landscape Of Pulmonary Artery Hypertension Associated With Congenital Heart Disease In Vietnam National Heart Institute – Bach Mai Hospital – Vietnam